Coagulation and flocculation treatment of wastewater in textile industry using chitosan - Abu Hassan, Mohd. Ariffin; Tan, Pei Li; Noor, Zainura Zainon (Faculty of Chemical and Natural Resources Engineering,Universiti Teknologi Malaysia, 2009)
Aluminum sulfate (alum), ferrous sulfate, ferric chloride and ferric chloro-sulfate were commonly used as coagulants. However, a possible link of Alzheimer’s disease with conventional aluminium based coagulants has become an issue in wastewater treatment. Hence, special attention has shift towards using biodegradable polymer, chitosan in treatment, which are more environmental friendly. Moreover, chitosan is natural organic polyelectrolyte of high molecular weight and high charge density which obtained from deacetylation of chitin. Experiments were carried out on textile industry wastewater by varying the operating parameters, which are chitosan dosage, pH and mixing time in order to study their effect in flocculation process by using chitosan. The results obtained proved that chitosan had successfully flocculated the anionic suspended particles and reduce the levels of Chemical Oxygen Demand (COD) and turbidity in textile industry wastewater. The optimum conditions for this study were at 30 mg/l of chitosan, pH 4 and 20 minutes of mixing time with 250 rpm of mixing rate for 1 minute, 30rpm of mixing rate for 20 minutes and 30 minutes of settling time. Moreover, chitosan showed the highest performance under these conditions with 72.5% of COD reduction and 94.9% of turbidity reduction. In conclusion, chitosan is an effective coagulant, which can reduce the level of COD and turbidity in textile industry wastewater